Preparation and Characterization of Novel Fe2O3-Flaky Coated Carbon Fiber by Electrospinning and Hydrothermal Methods - Qing-Yun Chen; Lang Liu; Yun-Hai Wang (Advances in Condensed Matter Physics)
A novel hierarchical nanostructure of Fe2O3-flaky coated carbon fibers was produced by the electrospinning process followed by a hydrothermal technique. First, electrospinning of a colloidal solution that consisted of ferric nitrate and polyacrylonitrile (PAN) was performed to produce PAN nanofibers. Then electrospun nanofiber was stabilized and calcinated in nitrogen at 800°C for 2 h to produce carbon nanofibers (CNFs) which were exploited to produce Fe2O3-flaky structure using hydrothermal technique. The as-obtained products were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results revealed that Fe2O3 flakes were successfully grown on the CNFs substrates, and the coverage of Fe2O3 flakes could be controlled by simply adjusting the hydrothermal pH value and time. Fe2O3-flaky coated carbon fibers displayed high photocatalytic activity toward degradation of methyl orange (MO) under visible light irradiation.